ANALISIS DAMPAK PUASA SENIN KAMIS TERHADAP KADAR KOLESTEROL DALAM DARAH MENGGUNAKAN ALAT UKUR NON-INVASIF BERBASIS ARDUINO UNO - Muhammad Labib; Farah Alfiana Na’ila; Lailiyatu Latifah; Heni Sumarti (Universitas Islam Negeri Alauddin Makassar, 2022)
Excessive cholesterol in the blood can have an impact on health, causing various deadly diseases. Fasting Monday and Thursday is one solution in lowering cholesterol levels in the blood apart from our main reason for worshiping Allah SWT. The purpose of this study was to determine the effect of fasting on Mondays and Thursdays on cholesterol levels in the blood using a non-invasive cholesterol level measuring instrument based on Arduino Uno. The method used is the Research and Development (R&D) method. The results showed that the non-invasive measuring instrument had an accuracy of 97.02%, so it was feasible to be used as a medical measuring instrument. Analysis of six respondents who did fasting Monday and Thursday shows a linear tendency to decrease cholesterol levels with an average coefficient of determination of 0.3282.